2014
DOI: 10.1021/jm5002937
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Pyrazolopyridones as a Novel Class of Noncovalent DprE1 Inhibitor with Potent Anti-Mycobacterial Activity

Abstract: A novel pyrazolopyridone class of inhibitors was identified from whole cell screening against Mycobacterium tuberculosis (Mtb). The series exhibits excellent bactericidality in vitro, resulting in a 4 log reduction in colony forming units following compound exposure. The significant modulation of minimum inhibitory concentration (MIC) against a Mtb strain overexpressing the Rv3790 gene suggested the target of pyrazolopyridones to be decaprenylphosphoryl-β-D-ribose-2'-epimerase (DprE1). Genetic mapping of resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 26 publications
1
57
0
1
Order By: Relevance
“…Of note, these compounds are the first non-nitro-benzothiazinones that demonstrate significant mycobacterial activity in vitro. Several noncovalent DprE1 inhibitors have been described recently (12,18,20,21,25), and these display MIC values close to those of PyrBTZ01 and PyrBTZ02 presented in this work. In particular, TCA1 (18) and the azaindoles (26) were reported to be efficacious in a mouse model of TB, although those compounds are less potent than BTZ043 or PBTZ169 in vitro (1,3).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of note, these compounds are the first non-nitro-benzothiazinones that demonstrate significant mycobacterial activity in vitro. Several noncovalent DprE1 inhibitors have been described recently (12,18,20,21,25), and these display MIC values close to those of PyrBTZ01 and PyrBTZ02 presented in this work. In particular, TCA1 (18) and the azaindoles (26) were reported to be efficacious in a mouse model of TB, although those compounds are less potent than BTZ043 or PBTZ169 in vitro (1,3).…”
Section: Discussionsupporting
confidence: 80%
“…One possible consequence of this would be the trifluoromethyl group failing to enter the pocket below Cys387 as deeply as the corresponding group on BTZ043 or PBTZ169. This pocket is lined by His132, Gly133, Lys134, Lys367, and Phe369, and the trifluoromethyl moiety forms van der Waals interactions with these residues, as well as forming a hydrogen bond with the amide of Asn385 (21,27). It is conceivable that the trifluoromethyl group on the pyrrole derivatives fails to make these interactions and this, especially the missing covalent semimercaptal bond, leads to PyrBTZ01 and PyrBTZ02 binding much more weakly to their target than do the nitro-benzothiazinones.…”
Section: Discussionmentioning
confidence: 99%
“…Several biochemical and structural biology studies have shown that BTZs are suicide inhibitors, whereby BTZ is activated by DprE1, a FAD-de-pendent enzyme, forming a covalent semimercaptal bond with a key active-site cystine residue (Trefzer et al 2010(Trefzer et al , 2012Batt et al 2012). Subsequent high-throughput screening and highcontent screening experiments have revealed that DprE1 is an extremely "druggable" enzyme, with molecules such as the dinitrobenzamides (DNBs), nitrotriazoles, pyrazolopyridones, azaindoles, and a benzothiazoles (TCA1) (Christophe et al 2009;Stanley et al 2012;Shirude et al 2013;Wang et al 2013;Panda et al 2014).…”
Section: Arabinan Precursor Synthesismentioning
confidence: 99%
“…22 After the incubation, determination of residual enzymatic activity conclusively indicated that, while BTZ043 led to an irreversible inhibition of DprE1, in vitro compound 3 reversibly inhibited the enzyme (Figure 4). Additionally, the MIC value of 3 was determined in the NTB1 strain (Cys387Ser mutation in DprE1) 23,24 that was shown to be resistant to BTZ043. Here also, 3 was found to be an effective inhibitor (Table 1), indicating that it is a reversible and noncovalent inhibitor of DprE1 (see SI).…”
Section: T Uberculosis (Tb) Is a Disease Mainly Caused Bymentioning
confidence: 99%